Mechanismbased role of the intestinal microbiota in gestational diabetes mellitus: A systematic review and meta-analysis - Yan, Min; Guo, Xiaoying; Ji, Guiyuan; Huang, Rui; Huang, Dongyi; Li, Zhifeng; Zhang, Dantao; Chen, Siyi; Cao, Rong; Yang, Xingfen; Wu, Wei (Frontiers in Immunology, 2023)
Background Metabolic disorders caused by intestinal microbial dysregulation are considered to be important causes of gestational diabetes mellitus (GDM). Increasing evidence suggests that the diversity and composition of gut microbes are altered in disease states, yet the critical microbes and mechanisms of disease regulation remain unidentified. Methods PubMed® (National Library of Medicine, Bethesda, MD, USA), Embase® (Elsevier, Amsterdam, the Netherlands), the Web of Science™ (Clarivate™, Philadelphia, PA, USA), and the Cochrane Library databases were searched to identify articles published between 7 July 2012 and 7 July 2022 reporting on case–control and controlled studies that analyzed differences in enterobacteria between patients with GDM and healthy individuals. Information on the relative abundance of enterobacteria was collected for comparative diversity comparison, and enterobacterial differences were analyzed using random effects to calculate standardized mean differences at a p-value of 5%. Results A total of 22 studies were included in this review, involving a total of 965 GDM patients and 1,508 healthy control participants. Alpha diversity did not differ between the participant groups, but beta diversity was significantly different. Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria were the dominant bacteria, but there was no significant difference between the two groups. Qualitative analysis showed differences between the groups in the Firmicutes/Bacteroidetes ratio, Blautia, and Collinsella, but these differences were not statistically different. Conclusion Enterobacterial profiles were significantly different between the GDM and non-GDM populations. Alpha diversity in patients with GDM is similar to that in healthy people, but beta diversity is significantly different. Firmicutes/Bacteroidetes ratios were significantly increased in GDM, and this, as well as changes in the abundance of species of Blautia and Collinsella, may be responsible for changes in microbiota diversity. Although the results of our meta-analysis are encouraging, more well-conducted studies are needed to clarify the role of the gut microbiome in GDM. The systematic review was registered with PROSPERO (https://www.crd.york.ac.uk/prospero/) as CRD42022357391.